Making politics go well down under : public journalism in New Zealand daily newspapers : a thesis presented in fulfilment of the requirements for the degree of Master of Management in Communication Management at Massey University, Wellington, New Zealand - Venables, David (Massey University, 2008)
The literature on the use of public journalism suggests that it can lead to different news coverage than is traditionally provided by the news media. Specifically, these differences have been identified in story content, use of different sources and use of mobilising information. This thesis asks whether such differences can be identified in newspapers’ coverage of the 2001 Local Body Elections in New Zealand. The research involved content analysis of New Zealand’s six largest daily newspapers, three of them with experience of using public journalism and three with no such experience. Interviews were also conducted with two or three senior journalists involved in organising each paper’s election campaign in order to explore their goals for the election coverage and evaluation of it. The results mirror those of previous research by showing significant differences in the coverage of the newspapers with public journalism experience in relation to some factors, but not others. The papers with a public journalism background consistently used more non-elite sources than the traditional papers, but did not consistently use more female sources. They also included mobilising information in stories more frequently and made greater use of story features, or “elements”, associated with public journalism. However, one of the papers with no experience of public journalism also ranked highly in relation to these two factors. The interviews revealed some differences in goals among the journalists, but this was not a simple split between the journalists on papers with public journalism experience and the other journalists. For example, not all interviewees working for the papers experienced in using public journalism agreed that their goal should be to boost voter turnout. Nor was an overt commitment to supporting the democratic process expressed only by staff on the papers with public journalism experience. The interviews did, however, identify that only the three newspapers with a public journalism background used polling to identify the issues that were important to the public and proceeded to cover these issues during their election campaign
Keywords: Public journalism; Communication management; Politics; Newspaper journalism; New Zealand; 2001 local body elections; Journalism; Fields of Research::420000 Language and Culture::420300 Cultural Studies::420304 Screen and media studies